1997
DOI: 10.1055/s-2007-972656
|View full text |Cite
|
Sign up to set email alerts
|

Bone Density and Bone Metabolic Markers in Active Collegiate Athletes: Findings in Long-distance Runners, Judoists, and Swimmers

Abstract: We investigated the bone metabolic system status of 103 male and female volunteer collegiate athletes, who were actively pursuing one of three different sports: Long-distance running (LR); judo (JU); and swimming (SW). The following parameters were evaluated: total body bone mineral density (TMBD); bone-forming metabolic markers; serum procollagen type I C-peptide (PICP) levels; bone alkaline phosphatase (B-ALP) content; bone resorption markers, urinary pyridinoline (Pyd) and deoxypyridinoline (Dpd) levels. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 2 publications
6
43
1
3
Order By: Relevance
“…Physical activity is the principal external regulator of bone mass but its influences on BMD rely on type of exercise as reported in previous cross-sectional researches (4,6,10,11,17). Our study found that TBMD of athletes engaging in weight-bearing sports was greater than non-athletic controls, and that of swimmers was slightly less than the controls after adjustment for weight.…”
Section: Discussionsupporting
confidence: 75%
“…Physical activity is the principal external regulator of bone mass but its influences on BMD rely on type of exercise as reported in previous cross-sectional researches (4,6,10,11,17). Our study found that TBMD of athletes engaging in weight-bearing sports was greater than non-athletic controls, and that of swimmers was slightly less than the controls after adjustment for weight.…”
Section: Discussionsupporting
confidence: 75%
“…This suggests that a 6-month volume-extended heavy training period positively affected bone formation markers without altering the whole body bone mass and BMD in elite athletes. Bone mineral density in our athletes was higher compared to results obtained from different endurance athletes such as triathletes (Maimoun et al 2004a(Maimoun et al , 2004b, cyclists (Maimoun et al 2004a;Stewart and Hannan 2000), or swimmers (Maimoun et al 2004a;Matsumoto et al 1997) but similar to runners (Bennell et al 1997;Brahm et al 1997) at the specific skeleton sites that are loaded during training. This further supports the importance of impact activity on bone development.…”
Section: Discussioncontrasting
confidence: 48%
“…Con respecto al programa de natación en la piscina profunda, hay diversidad de opiniones sobre si un programa de natación puede (Orwoll et al, 1989;Pinto et al, 2003;Taaffe et al, 1995;Tsukahara et al, 1994) o no (Courteix et al, 1998;Fehling et al, 1995;Heinrich et al, 1990;Matsumoto et al, 1997) mejorar el nivel de DMO. No se han encontrado estudios en los que evalúen el SI tras un programa de entrenamiento en piscina profunda como el que se ha hecho en este estudio.…”
Section: Discussionunclassified